2016
DOI: 10.1111/tan.12757
|View full text |Cite
|
Sign up to set email alerts
|

Association of rs6822844 within the KIAA1109/TENR/IL2/IL21 locus with rheumatoid arthritis in the Algerian population

Abstract: Increasing evidence suggests that the rs6822844, within KIAA1109/TENR/IL2/IL21 gene cluster on 4q27, is strongly associated with rheumatoid arthritis (RA) in the Caucasian population. The aim of this study is to investigate the possible association between the SNP rs6822844 and susceptibility to RA in the Algerian Maghreb population, and to explore the association with the clinical and immunological features of RA. The polymorphism rs6822844 was genotyped in 323 RA patients and 323 healthy individuals using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Zhernakova et al [26] detected a decrease in frequency of the rs6822844 T-allele in RA (14.1%), and demonstrated significant association between this polymorphism and RA susceptibility (OR = 0.72, 95% CI = 0.61-0.86, P < 0.001). Moreover, Louahchi et al [22] showed a protective effect of the minor T-allele (OR = 0.39, 95% CI = 0.26-0.57), whereas the major G-allele appeared to be a risk susceptibility (OR = 2.57, 95% CI = 1.74-3.83, P < 0.001). Nevertheless, Malinowski et al [24] examined 422 RA cases and 338 controls, and found that IL-21 rs6822844 was not risk loci for RA susceptibility.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Zhernakova et al [26] detected a decrease in frequency of the rs6822844 T-allele in RA (14.1%), and demonstrated significant association between this polymorphism and RA susceptibility (OR = 0.72, 95% CI = 0.61-0.86, P < 0.001). Moreover, Louahchi et al [22] showed a protective effect of the minor T-allele (OR = 0.39, 95% CI = 0.26-0.57), whereas the major G-allele appeared to be a risk susceptibility (OR = 2.57, 95% CI = 1.74-3.83, P < 0.001). Nevertheless, Malinowski et al [24] examined 422 RA cases and 338 controls, and found that IL-21 rs6822844 was not risk loci for RA susceptibility.…”
Section: Discussionmentioning
confidence: 96%
“…Among those, 11 articles were excluded for the following reasons: four articles were unrelated; five articles were excluded because they investigated diseases other than RA; one examined the IL-23R rs11209026 polymorphism, and one did not have complete genotype's information, three articles were classified to meta-analysis. Following the above screening, the remaining nine articles, comprising a total of 9998 cases and 10,742 controls, were selected for the meta-analysis ( Table 1 and Figure 1) [9,[19][20][21][22][23][24][25][26]. Seven studies evaluated Caucasian subjects and the remaining two investigated Asian subjects.…”
Section: Characteristics Of Selected Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…locusId=59067) and association of individual SNPs with autoimmune disorders such as systemic lupus erythematosus [17], graves disease [18]and in ammatory bowel disease [19,20] have been demonstrated. Various reports have shown a signi cant association of IL-21 polymorphisms and RA in different populations such as Netherlanders [21], Algerian [22], Columbian [19]. Further, a recent meta-analysis with including nine various studies [23] demonstrated decreased susceptibility of IL-21 rs6822844 polymorphism against the development of RA.…”
Section: Introductionmentioning
confidence: 98%